Feasibility study on establishing a silk filature plant for raw silk production - Abilay, Jose Marie M. (College of Engineering, 1994)
Market Study. The study shows that there is a substantial gap in the supply of raw silk in both the local and international market and this gap is increasing steadily. It has been determined that there are limited filature facilities in the country to address this gap. The analysis of the market potential of raw silk production from silkworm cocoons shows that the establishment of a filature plant would help in meeting this increasing demand. One critical factor which needs to be dealt with is the adequate supply of silkworm cocoons to assure continuous production of raw silk. Technical Study. The study on the cottage-type reeling machine's efficiency reveal that the machine developed by PTRI is still very crude and that the incidence of wastage, currently at 60 percent, is quite high. Presently, there are no alternatives in the market to these machines unless we are to import the equipment but this would require a large capital investment. Since the capacity of this machine is small (output=0.6 kg./day), for the project to be viable, at least five machines should be operated. Nevertheless, the quality of the raw silk produced is already good and can compete with the raw silk products of other countries. The filature plant will be located in Bacolod City, Negros Occidental since it is the most strategic location to meet both the target market and raw material sources. The supply of silkworm cocoons has been determined to be an important factor since there is presently a declining trend in its production. However, this is deemed temporary in lieu of the increasing hectarage of mulberry plantations as well as government efforts to boost the industry. Financial Study. The profit ratios computed show relatively high ROI and ROE figures. Also, the income for the projected five year period is increasing at a steady rate. Payback period is five (5) years. Socio Economic Study. As in any local business venture, the project will contribute to the country's economy by generating employment and earning funds for government projects through payment of taxes. The costs identified are negligible compared to the substantial benefits which could be generated from the project. This detailed feasibility study shows that the establishment of Prime Silk Enterprise for raw silk production is both viable and profitable. The proponents are thus encouraged to proceed with implementation.